The Role of Ethnobiology in Responding to Current Problems in the Management of Biological Resources and Ecosystems in Indonesia - Purwanto, Yohanes; Munawaroh, Esti; Ajiningrum, Purity Sabila; Sujarwo, Wawan (Advances in Social Sciences Research Journal, 2021)
ABSTRACT Ethnobiology is defined as the scientific study of the cultural knowledge possessed by various communities. It is also related to the techniques used in the management of biological resources, and the position of those communities in their cosmic cultural vision. This study discusses the role of development and perspectives of ethnobiology in Indonesia for managing the diversity of biological resources and their ecosystems sustainably. The results of ethnobiological studies can describe the problems, potentials, and opportunities to develop the diversity of biological natural resources and their ecosystems as a source of life for the community in a sustainable manner. The current problems faced in the management of biological resources are socio-culture, limitations and disregard for science and technology, weak institutions, inability to arrange spatial planning, inaccurate determination of development priorities, misperceptions and misconception about biodiversity, policy fragmentation and inability to manage biological resources, enforcement of certification, and climate change. Therefore, ethnobiological studies must be able to reveal the benefits and potentials of biological resources and their ecosystem and provide a foundation for the management and advancement of biodiversity sustainably to increase national prosperity and development. Keywords: Ethnobiology, Biodiversity, Management, Sustainability